2013
DOI: 10.1017/jfm.2012.501
|View full text |Cite
|
Sign up to set email alerts
|

On the self-propulsion of an -sphere micro-robot

Abstract: The aim of this paper is to describe the self-propulsion of a micro-robot (or microswimmer) consisting of N spheres moving along a fixed line. The spheres are linked to each other by arms with their lengths changing periodically. We use the asymptotic procedure containing the two-timing method and a distinguished limit. We show that self-propulsion velocity appears (in the main approximation) as a linear combination of velocities of all possible triplets of spheres. Velocities and efficiencies of three-, foura… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The closure equations 5 and 6 can be interpreted via a representation of the sperm as an extended object, consisting of K negligibly small spheres, where is the number of regularised Stokeslets in a single sperm. This is motivated by the commonly used simplification of sphere-linked swimmer models 45 47 , noting that the regularised Stokeslets are approximately singular Stokeslets, at least away from the singularity, and similarly Stokeslets are good approximations for spheres away from the very near field of the sphere.…”
Section: Methodsmentioning
confidence: 99%
“…The closure equations 5 and 6 can be interpreted via a representation of the sperm as an extended object, consisting of K negligibly small spheres, where is the number of regularised Stokeslets in a single sperm. This is motivated by the commonly used simplification of sphere-linked swimmer models 45 47 , noting that the regularised Stokeslets are approximately singular Stokeslets, at least away from the singularity, and similarly Stokeslets are good approximations for spheres away from the very near field of the sphere.…”
Section: Methodsmentioning
confidence: 99%
“…The frequency dependence of velocity -initial increase and subsequent decrease -is in qualitative agreement with the predictions of the simple model (Eqs. [1][2][3][4][5]. A more exact numerical simulation of the system, without free parameters, is described in the Appendix and shown by the dashed line in Figure 4.…”
Section: Throwersmentioning
confidence: 99%
“…The distance then increases with time as Y 5 − Y 5 0 ∼ t where Y 0 is the distance at the onset of the repulsive phase. The particle reaches a distance Y 1 at the end of the repulsive phase, Y 5 1 − Y 5 0 = C/ f , where the constant C depends on the strength and fraction of the repulsive interaction, as well as on hydrodynamic drag. The distance by which the particle moves is then ∆Y = (C/ f +Y 5 0 ) 1/5 −Y 0 .…”
Section: Omnidirectional Rowermentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of different micro-robots by the same method can be found in Vladimirov (2012bVladimirov ( ,c, 2013. In Vladimirov (2012a,d) the same form of TTM resulted in a new asymptotic model and a new equation for the averaged flows generated by acoustic waves and for MHD-flows.…”
Section: A Vladimirovmentioning
confidence: 99%